Horizontal arsC gene transfer among microorganisms isolated from arsenic polluted soil (2010)
The study of recent evolution of the arsC genes amplified from microorganisms inhabiting a Colombian oil-polluted soil with high concentrations of arsenic was performed through the isolation of 26 bacterial morphotypes resistant to 10 mM of arsenate. A 353 bp fragment of the gene coding for arsenate-reductase enzyme (i.e. arsC), and a 500 bp 16S rDNA partial sequence were sequenced for 16 morphotypes of the 26 previously isolated. arsC sequences clustered on the same clade with previously reported arsC chromosomal genes of Escherichia coli and Shigella sp.; while 16S rDNA sequences grouped within the genus Pseudomonas and Bacillus. The GC content and the Codon Adaptation Index (CAI) were calculated and statistically compared, both supported the previous results. The Isolation–Migration model (IM model) was applied to calculate the genetic flux between each clade defined by the phylogenetic analysis. In general, the existence of recent horizontal gene transfer (HGT) events was confirmed, and the presence of the arsC gene in Bacillus sphaericus is reported for the first time.